Studi Komparatif: Konflik Regional Tahun 1963–1966, Perspektif Buku Ajar Sejarah Nasional Indonesia & Malaysia - Afifah Aura Felisha; Nashar Nashar; Eko Ribawati (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
This study conducts a comparative analysis of how the Indonesia–Malaysia regional conflict of 1963–1966, known as Konfrontasi, is represented in the official national history textbooks of Indonesia and Malaysia. The research objects include Indonesia’s Sejarah Indonesia Kelas XII Kurikulum Merdeka (2022), Sejarah Indonesia Kelas XII Kurikulum 2013, and Malaysia’s Sejarah Tingkatan 5 KSSM (2020). Employing a qualitative comparative method with George Z.F. Bereday’s comparative analysis framework, the study examines narrative construction, ideological orientation, terminology selection, actor representation, and the influence of political interests on historical writing in educational contexts. The findings reveal significant divergences between the two countries’ textbooks: Indonesian textbooks tend to adopt a heroic-nationalist framing centered on Soekarno’s leadership and anti-neocolonial spirit, while Malaysia’s textbook emphasizes the communist threat narrative and international diplomatic resolution. The Kurikulum Merdeka textbook shows a marked reduction in Konfrontasi coverage compared to Kurikulum 2013, shifting from a heroic-expository approach to a more multi-perspectival and reflective framework. These differences reflect how ideological interests and bilateral political dynamics shape the construction of collective memory through formal education, highlighting the need for more balanced and transnational historical narratives in history education.